Disturbed Ca2+ homeostasis increases glutaminyl cyclase expression; connecting two early pathogenic events in Alzheimer's disease in vitro. - Line De Kimpe (Public Library of Science (PLoS), 2012)
A major neuropathological hallmark of Alzheimer's disease (AD) is the deposition of aggregated β amyloid (Aβ) peptide in the senile plaques. Aβ is a peptide of 38-43 amino acids and its accumulation and aggregation plays a key role early in the disease. A large fraction of β amyloid is N-terminally truncated rendering a glutamine that can subsequently be cyclized into pyroglutamate (pE). This makes the peptide more resistant to proteases, more prone to aggregation and increases its neurotoxicity. The enzyme glutaminyl cyclase (QC) catalyzes this conversion of glutamine to pE. In brains of AD patients, the expression of QC is increased in the earliest stages of pathology, which may be an important event in the pathogenesis. In this study we aimed to investigate the regulatory mechanism underlying the upregulation of QC expression in AD. Using differentiated SK-N-SH as a neuronal cell model, we found that neither the presence of Aβ peptides nor the unfolded protein response, two early events in AD, leads to increased QC levels. In contrast, we demonstrated increased QC mRNA levels and enzyme activity in response to another pathogenic factor in AD, perturbed intracellular Ca(2+) homeostasis. The QC promoter contains a putative binding site for the Ca(2+) dependent transcription factors c-fos and c-jun. C-fos and c-jun are induced by the same Ca(2+)-related stimuli as QC and their upregulation precedes QC expression. We show that in the human brain QC is predominantly expressed by neurons. Interestingly, the Ca(2+)- dependent regulation of both c-fos and QC is not observed in non-neuronal cells. Our results indicate that perturbed Ca(2+) homeostasis results in upregulation of QC selectively in neuronal cells via Ca(2+)- dependent transcription factors. This suggests that disruption of Ca(2+) homeostasis may contribute to the formation of the neurotoxic pE Aβ peptides in Alzheimer's disease.